Malawi : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2002)
This Selected Issues paper estimates the path of the equilibrium real exchange for Malawi. Based on a dynamic model of a small open economy, the paper identifies and discusses the dynamics between certain fundamental variables and the real exchange rate. It also investigates the presence of a long-term relationship between the real exchange rate and the explanatory variables, and estimates both the equilibrium real exchange rate and the speed at which it converges toward its equilibrium level. The paper also discusses episodes of discrepancies between the real effective exchange rate and its equilibrium level.